The effects of plyometric trainings on agility performances in male basketball players - Alp, M. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study was to investigate the effect of plyometric training on agility performance in male basketball players. Isparta Municipality Sports Club Basketball League Team participated in the study voluntarily with 24 people. Basketball players were randomly divided into two groups as normal training group (n = 12) and plyometric training group (n = 12). While the regular training group continued routine training, the other group received plyometric trainings in addition to routine trainings for 8 weeks, 3 days a week, at least 30 minutes a day. "T-Drill Test" was used to determine agility in both groups as at the beginning of the training period "pre-test" and "post-test" at the end. Data were analyzed by using statistical package program. Descriptive statistics were used for demographic information and "Paired t test" and "Independent t Test" were used for comparisons. Results were evaluated according to significance level of "0.05".There was no significant difference in Paired and Independent t Test results (p> 0.05). As a result, the reason for the lack of effect of plyometric training applied to male basketball players is that the athletes are able to reach maximum strength even in the pre-tests due to the practice of the training in the preparatory season, the minimal changes in the motor abilities of the athletes in the final tests and the frequency and duration of the plyometric trainings. It is recommended to increase the objectivity by considering these issues in future researches.